Socio-economic and macro-financial determinants and spatial effects on European private health insurance markets - Gabriela Mihaela Mureșan; Cristian Mihai Dragoş; Codruța Mare; Simona Laura Dragoș; Alexandra Pintea (Amfiteatru Economic Journal, 2021)
There is a great variation in the development of private health insurance (PHI) between European countries. Using data provided by Insurance Europe, World Bank and Standard and Poor's for 30 European countries, our research investigates the main factors influencing the size of these markets. In addition to some classical economic and social factors, the role of the size of national macrofinancial aggregates is also highlighted. In order to relax the constraints due to the multicollinearity phenomenon, we use as explanatory variables aggregated indicators, both calculated by financial institutions and by us, based on component items, used as proxy variables for different components of the financial system at national level. Using cross-section regressions with White corrections for heteroskedasticity and elements of spatial econometrics, we also analyze the possible phenomena of clustering and behavioural contagion between the countries in the sample.
Keywords: G22; C21; 330; private health insurance; White OLS; spatial econometrics; spatial contagion; clusterization